Cancer mortality in the indigenous population of coastal Chukotka, 1961–1990 - Dudarev, Alexy A.; Chupakhin, Valery; Odland, Jon Øyvind (International Journal of Circumpolar Health, 2013)
Objectives. The general aim was to assess the pattern and trend in cancer mortality among the indigenous people of coastal Chukotka during the period 1961 1990. Methods. All cases of cancer deaths of indigenous residents of the Chukotsky district in the northeasternmost coast of Chukotka Autonomous Okrug were copied from personal death certificates. There were a total of 219 cancer deaths during the study period. The average annual number of cases, percent, crude, and age-standardized cancer mortality rates (ASMR) per 100,000 among men and women for all sites combined and selected sites were calculated. Data were aggregated into six 5-year periods to assess temporal trends. Direct age-standardization was performed with the Segi-Doll world standard population used by the International Agency for Research on Cancer. Results. The indigenous Chukchi and Eskimo people living in Chukotsky district were at higher risk of death from cancer during the 30-year period between 1961 and 1990, with ASMR among men twice that of Russia, and among women 3.5 times higher. The excess can be attributed to the extremely high mortality from oesophageal cancer and lung cancer. Conclusions. The indigenous people of coastal Chukotka were at very high risk of death from cancer relative to the Russian population nationally. The mortality data from this study correspond to the pattern of incidence reported among other indigenous people of the Russian Arctic. Little information is available since 1990, and the feasibility of ethnic-specific health data is now severely limited.